PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 011 SUNGAI MAJO KECAMATAN KUBU KABUPATEN ROKAN HILIR - Sari, Lena Sari Lena; ', Zulkifli Zulkifli; ', Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This study originated from low IPS student learning outcomes, with theaverage grade 65.55. While the value of minimum completeness criteria (KKM)IPS is 68 This research is a class action (PTK). Aiming to improve learningoutcomes IPS 011 third grade students of SDN Majo River Kubu district of RokanHilir. Formulation of the problem: Is the application of Role Playing learningmodel to improve learning outcomes IPS 011 third grade students of SDN MajoRiver Kubu district of Rokan Hilir. Data were collected through observation usingthe observation sheet and learning outcomes through UH UH I and II. Thelearning outcomes that occurred from before held PTK with an average of65.55% with less category, while after the action research cycle 1 with anaverage of 70.5% with enough categories and the second cycle with an average83.75% with very good category. So improving student learning outcomes ofbasic score kesiklus an increase of 4.95% from the base score kesiklus while twoincreased to 13.25%. Activities that teachers who have an average amount in thefirst cycle with an average of 66.66 with both categories. Being the teacher'sactivities in the second cycle with an average of 91.66 with very good category.Activities of the student in cycle 1 was 62.5 in both categories, while the twocycles increased to 91.66. These results prove that the application of Role Playinglearning model to improve learning outcomes IPS third grade students of SDNSDN 011 River Majo Kubu district Rokan Hilir.Keywords: Role playing, IPS Learning Outcomes